ChemInform Abstract: Ruthenium(II)‐Catalyzed Selective Monoarylation in Water and Sequential Functionalizations of C—H Bonds. Issue 19 (18th April 2013) - Arockiam, Percia B.; Fischmeister, Cedric; Bruneau, Christian; Dixneuf, Pierre H.
Abstract The selective ortho monoarylation of functional arenes (I), (IV), and (VI) directed by N‐containing heterocyclic groups is achieved using a Ru‐catalyst in water.